2012
DOI: 10.1042/bj20111052
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PGE2 and the cAMP signalling pathway in the up-regulation of COX-2 and mPGES-1 expression in LPS-activated macrophages

Abstract: PG (prostaglandin) E2 plays an important role in the modulation of the immune response and the inflammatory process. In the present study, we describe a PGE2 positive feedback for COX (cyclo-oxygenase)-2 and mPGES-1 [microsomal PGES (PGE synthase)-1] expression in the macrophage cell line RAW 264.7. Our results show that PGE2 induces COX-2 and mPGES-1 expression, an effect mimicked by dbcAMP (dibutyryl-cAMP) or forskolin. Furthermore, the cAMP signalling pathway co-operates with LPS (lipopolysaccharide) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 58 publications
(95 reference statements)
5
67
2
Order By: Relevance
“…How this takes place is currently under study in our laboratory. Previous results from our laboratory indicate that macrophages' autocrine PGE 2 secretion is likely required to maintain gene expression of cytokines, Cox-2, and mPGES-1 (74). This might be equally true for signaling kinases like p110g.…”
Section: Discussionmentioning
confidence: 92%
“…How this takes place is currently under study in our laboratory. Previous results from our laboratory indicate that macrophages' autocrine PGE 2 secretion is likely required to maintain gene expression of cytokines, Cox-2, and mPGES-1 (74). This might be equally true for signaling kinases like p110g.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, several hundreds of genes showed changed expression in the tumor tissues from the EP2-knockout mice compared with tumor tissues from the wild-type mice. A reason for this could be that EP2 signaling in host tissues is involved in several different pathways that are important events in tumor cells associated with tumor progression, including angiogenesis, the upregulation of COX-2, the loss of E-cadherin expression and anti-apoptosis in stem cells (16,22,(25)(26)(27)(28). Prom-1, also known as CD133, and CD44 are well-known markers of cancer stem cells, indicating reduced gene expression in the tumor tissues from the EP2-knockout mice in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…5B). On the other hand, COX2 expression was found to be upregulated by directly binding CREB to a COX2 promoter (Diaz-Munoz et al 2012), which indicates that NF-kB may be the downstream molecule of the COX2 pathway and regulate ICAM1 expression only. Thus, selective COX2 inhibitor NS-398 was used and the phosphorylation level of NF-kB was determined.…”
Section: Pka-creb Participated In the Signaling Events Leading To Indmentioning
confidence: 99%